Pengaruh Religiusitas, Modernisasi, Pengetahuan Perpajakan Terhadap Kepatuhan Pajak dengan Kesadaran Wajib Pajak Sebagai Variabel Intervening - Mardini, Riyang; Fadilah, Sri (Universitas Teuku Umar, 2023)
Final PPH tax is one of the tax burdens that UMKM must pay to the government. The city of Bandung has the UMKM sector with the largest food and beverage sector in terms of tax revenue. This makes researchers want to examine the factors that influence tax compliance in UMKM in the food and beverage sector in the city of Bandung. Researchers used religiosity, modernization of the tax system, and taxpayer knowledge as independent variables, taxpayer compliance as the dependent variable, and taxpayer awareness as an intervening variable. The aim of this research is to determine the direct and indirect influence of variables that influence tax compliance. The research population is UMKM taxpayers. The data collection technique used is primary data with a questionnaire. The research approach used is a quantitative method, using multiple linear regression analysis using path analysis. The research results show that religiosity, modernization of the tax system, and taxpayer knowledge influence taxpayer compliance directly or through taxpayer awareness.